Role of artificial intelligence as a pedagogical tool in nursing training (Boletín Semillero de Investigación en Familia, 2024)
Currently, the inclusion of artificial intelligence (AI) in education emerges as a powerful tool promising to transform the teaching process. Through its capacity for personalization and immediate feedback, it offers a dynamic and adaptive approach to learning. However, it is essential to consider its implications, especially in fields like nursing, where human interaction is crucial. This article explores the advantages and challenges AI poses in education, highlighting the need for ethical and balanced use.
Keywords: Artificial intelligence, Health education, Nursing education.